Effect of filling percentage and raster style on tensile behavior of FDM produced PLA parts at different build orientation. (2022) - Singh, Jatinder; Kumar Goyal, Kapil; Kumar, Rakesh
Abstract: The most extensively adopted additive manufacturing process now a days is fused deposition modelling (FDM) due to its wide adaptability, rapid production, low maintenance and low cost. The parts produced through FDM process differs in strength due to wide variety of printing parameters. Thus, in this paper, an investigation has been performed to evaluate the effect of filling percentage and raster style on tensile property of PLA specimen build at horizontal, on-edge and vertical orientation using open-source 3D printer. Total 27 tensile specimen has been printed applying the full factorial design with three levels for three factors. Experimental results for ultimate tensile strength (UTS) revealed that raster style, filling percentage and build orientation effect the tensile characteristic significantly. ANOVA results confirms that the build orientation and filling percentage are most substantial parameters which impacts the tensile behavior of the FDM printed PLA parts as their p-values found to be < 0.05. Samples printed at on-edge position with concentric raster style shows maximum ultimate tensile strength of 32.34 MPA. The results also revealed that increase of filling percentage leads to increase of ultimate tensile strength.